TINGKAT KEGANASAN KANKER SERVIKS PASIEN PRA-RADIASI MELALUI PEMERIKSAAN AgNORs, MIB-1 DAN Cas- 3 - Kurnia, Iin; Bintari, Siti Harnina; Khaisuntaha, Mafaza (Biosaintifika: Journal of Biology & Biology Education, 2012)
Kanker serviks sering ditemukan di negara berkembang. Pengobatan kanker melalui radioterapi untuk mengetahui tingkat proliferasi dan mengurangi tingkat keganasan. Biomarker proliferasi dan apoptosis berupa AgNORs, MIB-1, dan Caspase 3. Namun belum dijelaskan mengenai korelasi ketiga biomarker dalam kaitannya dengan proliferasi dan apoptosis pada sel kanker serviks. Tujuan penelitian untuk mengetahui korelasi antara AgNORs, MIB-1, dan apoptosis pada kanker serviks. Penelitian observasional laboratoris menggunakan metode pewarnaan dengan menekankan kontras warna antara sitoplasma dan inti sel. Objek berupa sediaan mikroskopis dari 30 biopsi pasien kanker serviks. Pengambilan data dengan metode crocker dan blind manner. Analisis data menggunakan uji korelasi, dari ju mlah 21 pasien yang diamati menunjukkan. AgNORs dan MIB-1 memiliki angka relatif tinggi. Angka yang diperoleh ini berbanding terbalik dengan apoptosis yang relatif rendah. Korelasi antara AgNORs dengan MIB-1 menunjukkan r= 0,33 dan p= 0,15. AgNORs dengan apoptosis memiliki korelasi negatif yakni, r=-0,08 dan p= 0,73. MIB-1 dengan apoptosis memiliki korelasi negatif pula r= -0,18 dan p= 0,43. Kesimpulannya korelasi AgNORs dengan apoptosis memiliki kecenderungan lebih baik dari pada MIB-1 dengan apoptosis.Cervical cancer is often found in the developing countries. The treatment of cancer through radiotherapy was performed to determine the proliferation level and to reduce the malignancy level of cancer. The proliferation and apoptotic biomarkers were AgNORs, MIB-1, and Cas- 3. However, the correlation between the three biomarkers in relation to the proliferation and apoptosis in cervical cancer cells was not clear. The purpose of the study was to determine the correlation between AgNORs, MIB-1 and apoptosis in cervical cancer. This study was an observational research laboratory using a staining method to emphasize the color contrast between the cytoplasm and the nucleus of the cells. The microscopic preparations of the 30 patients with cervical cancer biopsies had been used as the study objects. Data was collected using the Crocker and Blind method and was then analyzed using correlation test. Data from 21 patients with AgNORs and MIB-1 showed a relatively high value. The figure obtained was inverse proportionally to the relatively low apoptotic value. The correlation between AgNORs and MIB-1 showed r = 0.33 and p = 0.15. There was negative correlation between AgNORs and apoptosis at r = -0.08 and p = 0.73. Meanwhile, between MIB-1 and apoptosis has also a negative correlation at r = -0.18 and p = 0.43. It was concluded that the correlation between AgNORs and apoptosis tended to be better than the MIB-1 and apoptosis.